2018
DOI: 10.1002/ccr3.1889
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, psychiatric, and neurological phenomena seen in mad honey disease: A clinical case report

Abstract: Key Clinical MessageMad Honey Disease is characterized by intoxication symptoms secondary to over‐ingestion of grayanotoxin found in honey produced from rhododendron nectar. Cardiovascular symptoms are common, but psychiatric and neurological phenomena are rarely seen in this condition. Our case details a patient who presented with florid symptomology in all three aforementioned areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…8 Gastrointestinal symptoms like nausea, vomiting, neurological symptoms like blurring of vision, ataxic gait, peripheral numbness, and psychiatric symptoms have also been reported from mad honey poisoning in Nepal. 9 Grayanotoxin levels can be measured in blood and urine. However, the facility to measure the toxin levels is not available in the many hospitals of Nepal including ours.…”
Section: Discussionmentioning
confidence: 99%
“…8 Gastrointestinal symptoms like nausea, vomiting, neurological symptoms like blurring of vision, ataxic gait, peripheral numbness, and psychiatric symptoms have also been reported from mad honey poisoning in Nepal. 9 Grayanotoxin levels can be measured in blood and urine. However, the facility to measure the toxin levels is not available in the many hospitals of Nepal including ours.…”
Section: Discussionmentioning
confidence: 99%
“…Mad honey, which is found in various types of rhododendron plants in the Eastern Black Sea region of Turkey, has been used for many years by the locals to treat diabetes, gastroduodenal maladies, and sexual dysfunction [ 3 ]. However, excessive consumption of this product can cause toxicity [ 4 ]. After the ingestion of wild honey, side effects such as exhaustion, dizziness, sweating, nausea, and vomiting occur.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic effects of honey can be dose-dependent, but the dose-response relationship was not evaluated conclusively; further research is indubitably warranted [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study with 150 positive individuals of COVID-19 showed 7% of death exhibited due to myocarditis with circulatory collapse, meanwhile, 33% myocarditis contributed towards the final severe outcome [ 72 ]. Honey is proved for its long-term cardiovascular benefits as well as short-term antiarrhythmic effects [ 73 ]. A decreased rate of cardiovascular disease is often associated with flavonoids for example anthocyanin and vitamins including niacin (B 3 ).…”
Section: Pharmacological Effects Of Honeymentioning
confidence: 99%